Cold welding of Ag nanowires by large plastic deformation. (15th March 2016) - Liu, Lei; Shen, Daozhi; Zou, Guisheng; Peng, Peng; Zhou, Y.
Abstract: The conventional cold welding concept was extended to nanoscale, in which silver nanowires were welded together by large plastic deformation. A nanoindenter was employed as a cold welding tool to visualize and conduct welding. The MD simulation shows that unlike single crystal nanowire, sufficient plastic deformation is key to realize successful welding when the two nanoobjects have large orientation mismatching. The lattice orientation of joint interface is complex but no defects were found in both experimental and simulation. Graphical abstract: